The prevalence of otitis media with effusion among kindergarten children in Kota Bharu - Hamzah, Mohamad; Noh, Lokman Md; Hassan, Hashim (1999)
Otitis Media With Effusion (OME) is a very common medical condition in temperate countries like America and Europe. In the United Kingdom the incidence among a group of children aged 5 to 7 years was 50%(1). In America OME is the most common cause of hearing loss among children. More than 30% of children will have I to 3 episodes of OME before the age of two years (2).In Denmark the incidence is 26% among a group of children aged 7 years(3).In these countries OME is a major health problem among children. Myringotomy was the most commonly performed operation among children in England and Wales in the seventies and was the main reason for admission to hospitals (4).Clinical experience denotes that this condition is not common in the tropics,including Malaysia.However,reports on incidence or prevalence of OME in this region has been very scarce. Being a relatively asymptomatic condition with a self-limiting natural history OME could easily be under-diagnosed and under-treated. Having detremental sequelae such as hearing loss (conductive and even sensorineural) and middle ear pathologies such as tympanic membrane atrophy, tympanosclerosis, perforations and cholesteatomas; it is very important to document the prevalence of OME in our country and to investigate for possible risk factors.